Bridging Vocation 4.0 Readiness: Needs Assessment of Interactive Simulation Media in Manufacturing-Focused Vocational High Schools - Nazli Nahrowi; Intan Nur Aisiah; Alivia Rizky Wulan Santoso; Chelsa Maya Arzanti (Journal on Smart Learning Technologies, 2025)
Digital transformation is essential for Vocational Education (SMK) to produce competitive graduates in the Industry 4.0 era, but there is a significant gap between the demands for practical skills and the dominant static teaching practices. This study aims to analyze the specific needs of digital learning media in Magetan Vocational High Schools (SMK) based on teacher and student perceptions. This study adopted a descriptive mixed-methods approach with a convergent triangulation design, chosen to validate and elaborate quantitative findings (student perceptions) with qualitative data (teacher context and barriers) in depth. Data were collected through a TPACK-based Media Needs Questionnaire (N=43 students) analyzed with percentages and averages, as well as semi-structured interviews (N=3 teachers) and observations of the learning environment, which were analyzed thematically. The results showed a sharp discrepancy: static media (PDF/PowerPoint) were rated the least effective (23.3%), while students collectively highly demanded Interactive Simulations/Virtual Laboratories (88.4%) and Project-Based Video Tutorials (81.4%). The implementation of these demands is hampered by systemic factors, particularly unstable infrastructure (internet/hardware), uneven distribution of teachers' pedagogical-technological competencies, and limited time for media development. This study concludes that the primary output of the needs analysis is the need to develop interactive simulation media oriented toward vocational practice. These findings provide an empirical basis for strategic policy revisions that focus on improving digital infrastructure and targeted teacher competency training to ensure effective and sustainable media adoption.